(untitled) (Economic and Political Thought, 2016)
The article distinguishes such risks for the credibility and effectiveness of NATO as a collective defence organisation in the short and medium term perspective, as tight defence budgets in key NATO countries, concentration of a large part of the members of NATO on other risks than those associated with Art. 5, the reduction of US involvement in European security connected with permanently unequal distribution of costs in NATO and changes in power in alliance countries that may undermine the transatlantic solidarity in the field of security. Referring to the theory of alliances and theories of deterrence the text argues that the credibility of alliance guarantee is always limited and is subject to significant fluctuations over time.